2021
DOI: 10.1186/s12967-021-03161-1
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of brain radiotherapy strategies on prognosis of patients with EGFR-mutant lung adenocarcinoma with brain metastasis

Abstract: Purpose Epidermal growth factor receptor (EGFR)-mutant lung cancers have a high risk of developing brain metastases (BM). Whole brain radiotherapy (WBRT), local radiotherapy, and WBRT + Boost are frequently used for treatment of BM. This retrospective study aimed to evaluate the difference in efficacy of these radiotherapy modes in patients with EGFR-mutant lung adenocarcinoma with BMs. Further, we determined the optimal radiotherapy regimen for patients based on Lung-molGPA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…A variety of clinical and pathological factors can affect the prognosis of EGFR-mutant lung adenocarcinoma with brain metastases. Therefore, we speculate that the heterogeneity of these factors between the two groups contributed to the lack of statistical difference in survival analysis (8,12,(25)(26)(27). We initially used a Chi-squared analysis to analyze whether there were differences in the general clinical characteristics between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of clinical and pathological factors can affect the prognosis of EGFR-mutant lung adenocarcinoma with brain metastases. Therefore, we speculate that the heterogeneity of these factors between the two groups contributed to the lack of statistical difference in survival analysis (8,12,(25)(26)(27). We initially used a Chi-squared analysis to analyze whether there were differences in the general clinical characteristics between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Lung-molGPA reportedly provides a better predictive value, suggesting that lung-molGPA can comprehensively and accurately reflect the prognosis of NSCLC complicated by brain metastases (24, 28-30). These also suggest the importance of individualized therapy for craniocerebral radiotherapy (12,(31)(32)(33). Moreover, most previous retrospective studies have shown that EGFR-TKI concurrently administered with radiotherapy was more effective than treatment with EGFR-TKI alone, which was not consistent with the results of our study (10,19,34,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A score of 0–4 indicated significant impact on OS in patients. The grouping standard referred to our team's previous study, which revealed that a statistical difference in median survival between the two groups of BM patients from EGFR-mutant lung adenocarcinoma with a score of 1–2 and a score of 2.5–4 [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the original publication [ 1 ] there was an incorrect funding section. The incorrect and correct funding information is published in this correction article.…”
Section: Correction To: J Transl Med (2021) 19: 486 Https://doiorg/101186/s12967-021-03161-1mentioning
confidence: 99%